ROCK GEOMETRY WITH COMPARISON TO POROSITY MEASUREMENT - Hamzah, Muhammad Haris (Universiti Teknology Petronas, 2012)
The oil and gas industry has been around for almost 150 years. It covers from the finding of hydrocarbon in remote locations all the way to producing and selling these rare and due to recent events in the world very expansive non-renewable energy source. The understanding of the relationship between pore geometry and porosity measurement is necessary in enabling us to further locate and predict new locations whereby oil and gas can accumulate. My project will be to see this relationship base on images obtained through thin sectioning and the Scanning Electron Microscope and compared to data obtained via the Mecury Porosimeter. Samples taken from the Semanggol Formation will consist of different types to obtain a number of readings. The results will enable us to better understand the relationship between pore geometry and porosity measurement